An integrated drinking water production system to remove chemical and microbiological pollution from natural groundwater by a coupled prototype helio-photochemical/H2O2/rapid sand filtration/chlorination powered by photovoltaic cell. (December 2018) - Alvear-Daza, John J.; Sanabria, Janeth; Gutiérrez-Zapata, Héctor M.; Rengifo-Herrera, Julián A.
Highlights: Successfully removal of 2, 4-dichlorophenoxyacetic acid from groundwater was achieved. E. coli and K. pneumoniae cells were also inactivated from well water samples. Addition of H2 O2 may lead an enhancement of photoinduced natural abiotic processes. Concentration of trihalomethanes was below 10 µg L −1 after chlorination treatment. Bacteria viability was strongly reduced at high sunlight irradiation doses. Abstract: This study evaluates the simultaneous removal of 2, 4-dichlorophenoxyacetic acid acid-2, 4-D at 70 μg L −1 and the viability decreasing of Escherichia coli and Klebsiella pneumoniae from real groundwater samples containing natural amounts of iron (0.39 mg L −1 ) and natural pH (7.31) in a coupled prototype system powered by a photovoltaic cell (SPh + LPh + H2 O2 + RSF + Cl) consisting of photochemical (using both natural sunlight (SPh) and UV-B + A + Visible lamp (LPh) and a 30-L Compound Parabolic Collector-CPC reactor), rapid sand filtration (RSF) and chlorination (Cl, adding of Ca(OCl)2 to get residual chlorine ranging between 0.2 and 0.6 mg Cl L −1 ) to drinking water production. Results showed that simple addition of H2 O2 10 mg L −1 and both natural sunlight and artificial light irradiation could enhance several natural photo-induced processes among them photocatalytic and photo-Fenton. These radicals could be responsible for both bacteria inactivation and 2, 4-D removal from natural groundwater diminishing the addition of substantial amounts of chemicals into water samples. Coupling of photochemical processes with conventional treatments to drinking water production as RSF and Cl at high solar energy dose (150, 000 J m −2 ), led to the efficient removal 2, 4-D and bacteria from natural groundwater without a significative trihalomethanes production. These results strongly suggest that coupling of helio-photochemical/H2 O2 systems with RSF and chlorination treatments seems to be a promising approach to remove chronic and acute risk from groundwater obtaining drinking water with high chemical and microbiological quality. However, despite these encouraging results, bacteria inactivation underwent a detrimental effect when low solar energy doses (75, 000 J m −2 ) were tested.